Lithium slag composite admixture, low-carbon lithium slag concrete and preparation method of low-carbon lithium slag concrete
By preparing a composite blend of zeolite and lithium slag-based negative calcium mesoporous silica, the problem of high SO3 content and insufficient activity in concrete is solved, and the high added value utilization of lithium slag and the improvement of concrete performance is achieved.
Patent Information
- Application Number
- CN202411905685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the prior art, there is a limit on the application of lithium slag in concrete. It is mainly because the high SO3 content in lithium slag causes the concrete to crack easily, insufficient activity leads to low strength, and the high water absorption rate of lithium slag affects the density and service life of the concrete.
By blending lithium slag with calcium hydroxide and baking, calcium-type lithium slag synthesized zeolite is prepared, and lithium slag-based negative calcium mesoporous silica is prepared by using the waste liquid during the preparation process to form a multi-composite blend to solve the problems of excessive SO3 content and insufficient activity.
It has achieved a large consumption and high application of lithium slag concrete, reduced the risk of cracking, improved the density and strength of concrete, extended the service life, and reduced solid waste environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a lithium slag composite admixture, a low-carbon lithium slag concrete and a preparation method thereof. Background Art
[0002] With the rapid development of electronic products and new energy vehicles, the demand for lithium has increased significantly. According to statistics, my country's annual demand for lithium carbonate exceeds 30,000 tons. The source of lithium carbonate mainly relies on the smelting of mineral lithium ore, and lithium ore will produce by-product lithium slag and waste slag during the smelting process. Lithium ore smelting is divided into two types according to different processes: lithium alkali method and lithium acid method. Among them, lithium acid smelting is the main source of existing lithium slag. The lithium acid process is to calcine spodumene ore at 1100~1300℃ in a rotary kiln and then use sulfuric acid method to produce lithium salt, and lithium slag is discharged in the process. According to statistics, the annual production and storage of lithium slag in previous years have reached tens of millions of tons, and the utilization rate is low. It not only occupies a large amount of land, but also causes serious pollution to water sources and the environment. Therefore, exploring the high added value of lithium slag has become a technical problem that needs to be solved urgently for the sustainable development of the lithium salt industry.
[0003] The chemical composition of lithium slag is mainly amorphous silicon dioxide (accounting for about 40-60%) and aluminum oxide (accounting for about 15-25%) and a small amount of iron components, calcium oxide, etc. It has good grindability and certain volcanic ash activity. When lithium slag is used as a cement admixture or mineral admixture to prepare concrete, it can undergo secondary hydration reaction with Ca(OH)2, the product of cement in the hydration process, which can improve the compressive strength of concrete and improve the microscopic morphology of concrete hydration products. However, there are many defects in the application of lithium slag in concrete. Its dosage should not be too large, usually not more than 30%. The main reasons are as follows: First, the SO3 content in lithium slag is relatively high (generally >6%). When the dosage is large, concrete is prone to poor stability and high risk of cracking. Second, the activity of lithium slag mainly depends on secondary hydration reaction. When the dosage is large, the alkalinity and pH value of the hydration environment are reduced, the activity of lithium slag cannot be fully exerted, and the early and late strength of concrete are both low. Third, the microscopic morphology of lithium slag particles is a "rod-shaped" porous structure, which leads to a large water absorption rate of lithium slag (>15%) and has no lubricating effect on cement paste, affecting the workability of concrete.
[0004] In the prior art, the amount of lithium slag used in concrete is usually relatively small, and most of the technical improvements focus on solving the problem of lithium slag's easy water absorption, without fully considering the risk of cracking caused by the high SO3 content of lithium slag. Chinese patent CN111646773A discloses a method for preparing lithium slag concrete, which forms CSH and other substances on the surface of lithium slag through the composite action of an activator and a coupling agent to fill the lithium slag pore structure and reduce the water absorption of lithium slag, but does not consider the problem of high SO3 content of lithium slag; Chinese patent CN115872695B discloses a lithium mica slag concrete, which "coats" and modifies lithium mica tailings, and uses a series of air entraining agents and admixtures to avoid the free sodium, potassium, and sulfate from affecting the performance of concrete, but the technical solution only adds 1.5-2.5 weight components of lithium slag, which is basically not used as an admixture. Not only does it need to modify the lithium slag powder, but it also needs to specially prepare the air entraining agent and admixture, and the technical solution is complicated.
[0005] Therefore, in order to achieve large-scale consumption of lithium slag solid waste and its large-volume application in concrete, it is necessary to fully consider and effectively solve a series of key application technical problems such as high risk of concrete cracking due to high SO3 content in lithium slag and poor concrete compactness due to insufficient activity, so as to improve the comprehensive performance of lithium slag admixture concrete, improve the safety of engineering structure use and extend its service life, and reduce solid waste environmental pollution. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, one of the objects of the present invention is to provide a method for preparing a low-carbon lithium slag composite admixture. The present invention utilizes lithium slag to prepare synthetic zeolite, and further utilizes the waste liquid generated in the preparation process of calcium-type lithium slag synthetic zeolite to prepare lithium slag-based negative calcium mesoporous silica, and mixes it with original lithium slag to form a multi-component composite admixture, which not only solves the problem of excessively high SO3 content in lithium slag concrete at a large dosage, but also solves the technical defects of insufficient lithium slag activity and low concrete strength, effectively reduces the risk of cracking of lithium slag concrete, comprehensively improves the density and working performance of lithium slag concrete, realizes the high value-added resource utilization of lithium slag solid waste, and meets the national strategic goal of low carbon.
[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0008] A method for preparing a low-carbon lithium slag composite admixture comprises the following steps:
[0009] S1. The lithium slag and calcium hydroxide are blended and ball-milled and then calcined and then ground to obtain a powder;
[0010] S2. The powder obtained in step S1 is mixed with water, calcium aluminate and EDTA are added to adjust the molar ratio of Si / Al to obtain a mixture, and then a silane coupling agent solution is added, mixed evenly, aged and then crystallized, and a solid product and a waste liquid are obtained by filtration. The solid product is washed and dried to obtain a calcium-type lithium slag synthetic zeolite;
[0011] S3. adjusting the pH value of the waste liquid obtained in step S2 to 6-7, filtering and taking the filtrate, and adjusting the pH value of the filtrate to 3-5 to obtain a silica sol; adding the silica sol to a hexadecyltrimethylammonium bromide solution, adjusting the pH value of the mixed solution to 9-10, and then performing a polycondensation reaction, separating and washing to obtain a solid product, and then subjecting the solid product to a high temperature reaction to obtain mesoporous silica;
[0012] S4. The mesoporous silica obtained in step S3 is added to a Ca(NO3)2 aqueous solution, and filtered after ultrasonic dispersion. The solid product is washed and dried to obtain a lithium slag-based calcium-negative mesoporous silica;
[0013] S5. The calcium-type lithium slag synthetic zeolite, lithium slag-based negative calcium mesoporous silica and original lithium slag are mixed in a mass ratio of 1:(2-6):(30-80) to obtain the composite admixture.
[0014] Lithium slag contains a large amount of silicon, aluminum and other elements, which can be used as a raw material for synthetic zeolite. Compared with conventional synthetic zeolite, the alkali metal oxide (Li2O) in lithium slag can act as a flux in the crystallization process to reduce the reaction temperature. At the same time, the trace active components (lithium and sodium ions) in lithium slag can be used as crystallization promoters to improve the structural integrity of synthetic zeolite, and the alkali metal ions can occupy the zeolite framework sites, so that the synthetic zeolite has more active sites and higher ion exchange capacity. In the preparation process of calcium-type lithium slag synthetic zeolite, lithium slag and calcium hydroxide are first subjected to high-energy ball milling, and mechanical force is used to remove large particle impurities, break the chemical bonds in lithium slag and increase the physical reaction surface area, and promote the full contact between lithium slag and calcium hydroxide; high-temperature reactor roasting and stirring can be used to fully melt the amorphous SiO2 and Al2O3 in the lithium slag to form aluminate and silicate ions, and form soluble calcium silicate and calcium aluminate with calcium ions in calcium hydroxide. During the hydrothermal crystallization process, EDTA improves the dissolution efficiency of calcium aluminate, and additional calcium aluminate is added to adjust the Si / Al ratio. Silane coupling agent can achieve a cross-linking effect. Silane hydrolysis produces active hydroxyl (Si-OH) groups, which can form Si-O-Si and Al-O-Si bond cross-linking bridges with Si-O bonds and aluminum oxygen (Al-O) bonds in the zeolite framework, thereby enhancing the stability of the zeolite framework. The bridging effect can effectively prevent the zeolite from deconstructing or dissolving in an alkaline environment, thereby improving the alkali resistance of the synthetic zeolite. In addition, a large amount of calcium ions are introduced into the structure of the synthetic zeolite during the alkali melting stage and the hydrothermal crystallization stage. When the synthetic zeolite is added to the concrete, a large amount of free calcium ions will also be generated. The double charge characteristics of calcium ions can enhance the oxygen bond strength of the zeolite compared to monovalent cations, and reduce the relaxation effect of the bonds in the crystal framework. The above two aspects comprehensively enhance the stability and strength of the synthetic zeolite framework in an alkaline environment, and improve the adsorption and fixation ability of the synthetic zeolite for sulfate ions in concrete. In this way, a calcium-type calcium-type lithium slag synthetic zeolite with higher selectivity and adsorption capacity for sulfate polyvalent anions is prepared.
[0015] The lithium slag composite admixture of the present invention contains a large amount of original lithium slag, and the lithium slag added to the concrete will produce a large amount of free SO4 2- ions, which causes concrete to expand and crack easily. The calcium-type lithium slag synthetic zeolite prepared by the present invention has a high ion exchange capacity and is resistant to polyvalent anions SO4 2- With higher selectivity, SO4 2- Adsorbed in the porous structure of calcium-type lithium slag synthetic zeolite, at the same time, the free calcium ions around the synthetic zeolite can form calcium sulfate precipitation with sulfate ions, solidify sulfate ions, and make SO4 2- The concentration is greatly reduced, reducing the technical problem of high SO3 content in lithium slag concrete with large dosage, which causes the concrete to expand and crack easily.
[0016] The waste liquid generated during the preparation of calcium-type lithium slag synthetic zeolite contains rich soluble silicates (SiO3 2- ) and aluminates (AlO2 - ), its silicate can be used as the silicon source precursor of mesoporous silica, and the use of waste liquid to prepare mesoporous silica can achieve further efficient utilization of lithium slag solid waste. In the preparation process of lithium slag-based mesoporous silica, the dissolved aluminate (AlO2 - ) will be converted into Al(OH)3 precipitation, and other impurities can also be precipitated, while silicate remains dissolved. This step effectively reduces impurities in mesoporous silica. Under acidic conditions, silicate can polymerize to form silica sol. CTAB dissolved in water will combine into spherical or rod-shaped microstructures to form pores. The mixed solution is adjusted with dilute ammonia water. Under alkaline conditions, silicic acid (Si(OH)4) will undergo hydrolysis and condensation reactions to form an ordered silicon-oxygen skeleton. Finally, after calcination, the bubbles formed by CTAB are removed to retain a uniform and stable mesoporous silica structure. Mesoporous silica is mixed with calcium nitrate aqueous solution, and calcium ions are coordinated with the silanol groups (Si-OH) on the surface of the mesoporous silica to achieve calcium ion loading on the mesoporous silica, while nitrate ions will not be directly adsorbed on the surface of the mesoporous material.
[0017] Mesoporous silica has a regular mesoporous structure with longitudinal channels. The high specific surface area can provide more active sites, which can react quickly with Ca(OH)2 in concrete to generate more dense CSH gel and accelerate the hydration process. In addition, the mesoporous structure can regulate the migration and distribution of water inside the concrete, prolong the hydration time, play an internal curing effect, and improve the mechanical properties and durability of concrete. The surface of negative calcium mesoporous silica is loaded with a large amount of calcium ions. Under alkaline conditions, the rich calcium ions can react with the silicate bound to the mesoporous surface or pores and the OH in the solution. - The reaction generates calcium hydroxide, increases the alkalinity of the solution and achieves the alkali excitation effect, accelerates the depolymerization of the O-Si-O bonds and Al-O-Si-O bonds in the lithium slag, and promotes the volcanic ash reaction of the lithium slag. At the same time, the free calcium ions in the mesoporous silica and synthetic zeolite can effectively increase the nucleation sites of CSH in the concrete, and comprehensively improve the reaction activity of the lithium slag and the density of the concrete.
[0018] Preferably, in step S1, the mass ratio of analytically pure calcium hydroxide to lithium slag is 1:(0.5-1); ball milling uses a planetary ball mill at a rotation speed of 400-500 rpm;
[0019] Preferably, the calcination temperature is 550-600° C. and the calcination time is 100-120 min.
[0020] Preferably, in step S2, the molar ratio of Si / Al is (2-3):1, and the mass of EDTA is 5%-10% of the mass of calcium aluminate.
[0021] Preferably, the concentration of the silane coupling agent solution is 10wt%~12wt%, and the mass ratio of the mixture to the silane coupling agent solution is (4~6):1.
[0022] Preferably, the silane coupling agent includes at least one of chlorotrihexylsilane, KH550, and KH570.
[0023] Preferably, in step S3, the temperature of the polycondensation reaction is 40-50° C., and the mixture is stirred for 10-14 hours and then allowed to stand for 10-14 hours.
[0024] Preferably, in step S3, the temperature of the high temperature reaction is 500-600° C., and the time is 5-6 hours.
[0025] Preferably, in step S4, the mass ratio of the mesoporous silica to the Ca(NO3)2 aqueous solution is 1:(2-3), and the concentration of the Ca(NO3)2 aqueous solution is 0.7-1.0 mol / L.
[0026] Preferably, the specific surface area of the original lithium slag is 400-600m 2 / kg, the specific surface area of the calcium type lithium slag synthetic zeolite is 3000-4000 m 2 / kg, the specific surface area of the lithium slag-based negative calcium mesoporous silica is 11000-13000 m 2 / kg. The formed lithium slag composite admixture realizes a hierarchical particle filling system. The nano-scale mesoporous silica particles fill the micron-scale harmful pores in the cement matrix, effectively enhancing the density and comprehensively improving the early and late strength of concrete.
[0027] Another object of the present invention is to provide a low-carbon lithium slag composite admixture prepared by the preparation method, wherein the composite admixture comprises calcium-type lithium slag synthetic zeolite, lithium slag-based negative calcium mesoporous silica and original lithium slag.
[0028] Another object of the present invention is to provide a lithium slag concrete made by using the low-carbon lithium slag composite admixture, comprising the following components in parts by weight: 100-150 parts of cement, 325-440 parts of low-carbon lithium slag composite admixture, 10-15 parts of corn protein solution, 950-1100 parts of crushed stone, 700-780 parts of sand, 140-155 parts of water, and 6-9 parts of water reducer.
[0029] The corn protein solution is prepared by mixing analytically pure corn protein with (80-90) wt% ethanol solution in a mass ratio of (0.5-1.0):9.5.
[0030] The preparation method of lithium slag concrete of the present invention comprises the following steps:
[0031] M1. Weigh each component by weight;
[0032] M2. The low-carbon lithium slag composite admixture is mixed with 1 / 3 water reducer and 1 / 3 water, ultrasonically mixed for 1-2 minutes, and then the corn protein solution is added and mixed evenly, and then cement, gravel, sand, 2 / 3 water reducer and 2 / 3 water are added and mixed evenly to obtain a concrete slurry.
[0033] The invention firstly ultrasonically mixes a low-carbon lithium slag composite admixture with a part of a water reducing agent and water to improve the dispersibility of the lithium slag composite admixture, and then mixes the mixture with a corn protein solution. The corn protein can form a coating film, is almost insoluble in water, and is soluble in an alkaline aqueous solution with a pH value of more than 11.5. The corn protein solution, the lithium slag composite admixture and water are mixed to achieve that the lithium slag composite admixture absorbs a part of water and then seals it. In the concrete mixing process, the lithium slag composite admixture no longer absorbs too much water, and does not affect the flowability of the lithium slag concrete. In the later coagulation and hardening process, as the alkalinity inside the concrete is continuously hydrated and increases, the alkalinity inside the concrete rises to more than 12, and the corn protein is dissolved, which does not affect the cement-based secondary hydration participation of the lithium slag rich composite admixture.
[0034] Compared with the prior art, the present invention is beneficial in that:
[0035] (1) The present invention uses calcium-type lithium slag synthetic zeolite prepared from lithium slag, lithium slag-based negative calcium mesoporous silica prepared from waste liquid generated in the process of preparing synthetic zeolite, and original lithium slag to form a multi-component composite admixture. Under the synergistic effect of various components, it not only solves the problem of excessively high SO3 content in concrete with a large amount of lithium slag admixture and easy cracking of concrete, but also solves the technical defects of insufficient lithium slag activity and low concrete strength, thereby realizing high value-added resource utilization of lithium slag solid waste.
[0036] (2) The calcium-type lithium slag synthetic zeolite prepared from lithium slag in the present invention has high structural integrity, more active sites and higher ion exchange capacity. The cross-linking effect of the silane coupling agent and the introduction of a large amount of calcium ions in the alkaline melting and hydrothermal crystallization stages enhance the stability and strength of the synthetic zeolite framework in an alkaline environment, and improve the adsorption and fixation capacity of the synthetic zeolite for sulfate ions in concrete, thereby preparing a calcium-type lithium slag synthetic zeolite with higher selectivity and adsorption capacity for sulfate polyvalent anions. The calcium-type lithium slag synthetic zeolite brings the original lithium slag to the SO4 2- Fixed in its porous structure, while the free Ca attached to the zeolite surface 2+ With SO4 2- Form CaSO4 precipitation, effectively reducing SO4 in concrete 2-concentration.
[0037] (3) The waste liquid generated during the preparation of calcium-type lithium slag synthetic zeolite contains rich soluble silicates, which can be used as a silicon source for mesoporous silica to achieve efficient utilization of waste. Calcium nitrate is mixed with mesoporous silica to achieve the loading of calcium ions on mesoporous silica. The regular mesoporous structure and high specific surface area of mesoporous silica provide more active sites, which react rapidly with Ca(OH)2 in concrete to generate more and denser CSH gels, accelerating the hydration process. Original lithium slag, calcium-type lithium slag synthetic zeolite, and lithium slag-based negative calcium mesoporous silica work together to realize a hierarchical particle filling system, further enhancing the density. The mesoporous structure can regulate the migration and distribution of water inside the concrete, achieving an internal curing effect. The surface of negative calcium mesoporous silica carries a large amount of calcium ions. Under alkaline conditions, the rich calcium ions can react with silicate groups bound to the mesoporous surface or pores and OH in the solution. - Reaction to generate calcium hydroxide, increase the alkalinity of the solution and achieve alkali excitation effect, and promote the lithium slag volcanic ash reaction. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] In the following examples and comparative examples, lithium slag is a byproduct produced in the process of producing lithium sulfate by calcining spodumene using a sulfuric acid method; the density of the lithium slag is 2.3-2.4 g / m 3 , its specific surface area is 400~600m 2 / kg.
[0040] The lithium slag concrete of the present invention comprises the following components in parts by weight: 100-150 parts of cement, 325-440 parts of low-carbon lithium slag composite admixture, 10-15 parts of corn protein solution, 950-1100 parts of crushed stone, 700-780 parts of sand, 140-155 parts of water, and 6-9 parts of water reducing agent;
[0041] Among them, cement is ordinary Portland cement P•O 42.5; sand can be natural river sand and / or artificial sand. When it is a mixture of natural river sand and artificial sand, the mass ratio of artificial sand to natural river sand is (2~3):(7~8), the fineness modulus of natural sand is 2.8~3.2, the fineness modulus of artificial sand is 2.7~3.0, and the stone powder content is less than 10%; the crushed stone is a continuous graded crushed stone of 5~25mm; the water reducer is a polycarboxylic acid water reducer, the water reduction rate is 35%, and the solid content is 37%.
[0042] Example 1
[0043] This embodiment provides a low-carbon lithium slag composite admixture, and the preparation method thereof comprises the following steps:
[0044] S1. Lithium slag and analytically pure calcium hydroxide were added to a ball mill in a mass ratio of 1:1 and milled for 20 minutes. The mixture was added to a high temperature reactor and calcined at 550°C for 120 minutes while stirring. After cooling, the molten mixture was ground and passed through a 200 mesh sieve to obtain a powder.
[0045] S2. Add deionized water at a solid-liquid ratio of 1:8 and stir evenly, then add calcium aluminate to adjust the Si / Al molar ratio to 2:1, and add EDTA at a concentration of 10% by mass of calcium aluminate, stir for 20 minutes to obtain a mixture, then add 10wt% chlorotrihexylsilane solution, the mass ratio of the mixture to the chlorotrihexylsilane solution is 5:1, mix evenly and let stand for 10 hours, then place in a 100°C crystallization kettle for crystallization for 8 hours, and obtain a solid product and waste liquid after filtration. The solid product is washed to a pH value of 6.5-7.5 and then dried to obtain a calcium-type lithium slag synthetic zeolite; the specific surface area of the calcium-type lithium slag synthetic zeolite is 3000-4000 m 2 / kg, micropores with pore size distribution of 0.5~1nm;
[0046] S3. Adjust the pH value of the waste liquid obtained in step S2 to 6-7, precipitate aluminate therein, obtain a relatively pure silicate solution by filtration, add dilute hydrochloric acid to adjust the pH value of the silicate solution to 4, obtain silica sol, wash the silica sol with deionized water, dry to constant weight, and set aside; then add the above silica sol to a 0.1 mol / L hexadecyltrimethylammonium bromide solution, the analytical pure mass ratio of silica sol to CTAB is 10:1, adjust the pH value of the mixed solution to 10 with dilute ammonia water, stir at 40°C for 12 hours and then stand for 12 hours, separate after polycondensation reaction, wash with deionized water and ethanol to obtain a solid product, then roast the solid product at 550°C for 6 hours, take out and cool to room temperature to obtain mesoporous silica;
[0047] S4. The mesoporous silica obtained in step S3 is added to a 0.7 mol / L Ca(NO3)2 aqueous solution, wherein the mass ratio of the mesoporous silica to the Ca(NO3)2 aqueous solution is 1:2, and the mixture is ultrasonically dispersed for 20 min and stirred for 4 h. The solid product is filtered out and washed and dried to obtain lithium slag-based negative calcium mesoporous silica. The specific surface area of the lithium slag-based negative calcium mesoporous silica is 11000~13000 m 2 / g.
[0048] S5. The calcium-type lithium slag synthetic zeolite, the lithium slag-based negative calcium mesoporous silica and the original lithium slag are mixed in a mass ratio of 5:20:300 to obtain a composite admixture.
[0049] Example 2
[0050] This embodiment provides a low-carbon lithium slag composite admixture, and the preparation method thereof comprises the following steps:
[0051] S1. Lithium slag and analytically pure calcium hydroxide were added to a ball mill in a mass ratio of 1:0.5 and milled for 30 minutes. The mixture was added to a high temperature reactor and calcined at 600°C for 100 minutes while stirring. After cooling, the molten mixture was ground and passed through a 200 mesh sieve to obtain a powder.
[0052] S2. Add deionized water at a solid-liquid ratio of 1:6 and stir evenly, then add calcium aluminate to adjust the Si / Al molar ratio to 3:1, and add EDTA at a mass ratio of 5% by mass of calcium aluminate, stir for 30 minutes to obtain a mixture, then add a KH550 solution with a concentration of 12wt%, the mass ratio of the mixture to the KH550 solution is 6:1, mix evenly and let stand for 10 hours, then place in a 90°C crystallization kettle for crystallization for 10 hours, filter to obtain a solid product and waste liquid, wash the solid product to a pH value of 6.5-7.5 and then dry to obtain a calcium-type lithium slag synthetic zeolite; the specific surface area of the calcium-type lithium slag synthetic zeolite is 3000-4000 m 2 / kg, micropores with pore size distribution of 0.5~1nm;
[0053] S3. Adjust the pH value of the waste liquid obtained in step S2 to 6-7, precipitate the aluminate therein, obtain a relatively pure silicate solution by filtration, add dilute hydrochloric acid to adjust the pH value of the silicate solution to 5, obtain silica sol, wash the silica sol with deionized water, dry to constant weight, and set aside; then add the above silica sol to a 0.2 mol / L hexadecyltrimethylammonium bromide solution, the analytical pure mass ratio of silica sol to CTAB is 10:1, adjust the pH value of the mixed solution to 9 with dilute ammonia water, stir at 50°C for 12 hours and then stand for 12 hours, separate after polycondensation reaction, wash with deionized water and ethanol to obtain a solid product, then roast the solid product at 600°C for 5 hours, take out and cool to room temperature to obtain mesoporous silica;
[0054] S4. The mesoporous silica obtained in step S3 is added to a 1.0 mol / L Ca(NO3)2 aqueous solution, the mass ratio of mesoporous silica to Ca(NO3)2 aqueous solution is 1:3, ultrasonic dispersion is performed for 30 min, stirring is performed for 3 h, the solid product is filtered out, and after washing and drying, lithium slag-based negative calcium mesoporous silica is obtained; the specific surface area of lithium slag-based negative calcium mesoporous silica is 11000~13000 m 2 / g;
[0055] S5. The calcium-type lithium slag synthetic zeolite, the lithium slag-based negative calcium mesoporous silica and the original lithium slag are mixed in a mass ratio of 5:20:300 to obtain a composite admixture.
[0056] Example 3
[0057] The low-carbon lithium slag composite admixture of this embodiment is basically the same as that of Example 1, with the only difference being that the mass ratio of the calcium-type lithium slag synthetic zeolite, the lithium slag-based negative calcium mesoporous silica and the original lithium slag is 10:30:400.
[0058] Comparative Example 1
[0059] The lithium slag composite admixture of this comparative example is obtained by mixing synthetic zeolite, mesoporous silica and original lithium slag in a mass ratio of 5:20:300.
[0060] The synthetic zeolite used in this comparative example is Y-type synthetic zeolite produced by Shandong Hefa Environmental Protection Technology Co., Ltd., with an effective ingredient content of 99%, a relative crystallinity of 80-88%, and a total specific surface area of 350-400 m 2 / g; mesoporous silica is mesoporous silica powder produced by Beijing Zhongke Keyou Technology Co., Ltd., with a specific surface area of 11000-12000 m 2 / kg.
[0061] Comparative Example 2
[0062] The low-carbon lithium slag composite admixture of this comparative example is basically the same as that of Example 1, except that sodium hydroxide is used to replace calcium hydroxide, and sodium aluminate is used to replace calcium aluminate.
[0063] Comparative Example 3
[0064] The low-carbon lithium slag composite admixture of this comparative example is substantially the same as that of Example 1, except that no chlorotrihexylsilane solution is added.
[0065] Comparative Example 4
[0066] The low-carbon lithium slag composite admixture of this comparative example is substantially the same as that of Example 1, except that step S4 is omitted.
[0067] Example 4
[0068] This embodiment provides a lithium slag concrete, comprising the following components in parts by weight: 150 parts of cement, 325 parts of the low-carbon lithium slag composite admixture of Example 1, 10 parts of corn protein solution, 1100 parts of crushed stone, 700 parts of sand, 140 parts of water, and 9 parts of a water reducing agent;
[0069] The corn protein solution is prepared by mixing analytically pure corn protein with 80 wt % ethanol solution in a mass ratio of 0.5:9.5.
[0070] The preparation method of lithium slag concrete of this embodiment comprises the following steps:
[0071] M1. Weigh each component by weight;
[0072] M2. Mix the low-carbon lithium slag composite admixture, 1 / 3 water reducer and 1 / 3 water, and mix them with an ultrasonic mixer at an ultrasonic frequency of 24 kHz for 1-2 minutes to improve the dispersibility of the low-carbon lithium slag composite admixture. Then add the corn protein solution and mix evenly. Then add cement, gravel, sand, 2 / 3 water reducer and 2 / 3 water, mix evenly, and obtain concrete slurry.
[0073] Example 5
[0074] This embodiment is basically the same as Embodiment 4, except that the low-carbon lithium slag composite admixture of Embodiment 2 is used instead of the low-carbon lithium slag composite admixture of Embodiment 1.
[0075] Example 6
[0076] This embodiment is basically the same as Embodiment 4, except that the lithium slag concrete of this embodiment includes the following components in parts by weight: 100 parts of cement, 440 parts of the low-carbon lithium slag composite admixture of Embodiment 3, 15 parts of corn protein solution, 950 parts of crushed stone, 780 parts of sand, 155 parts of water, and 6 parts of water reducer.
[0077] Comparative Example 5
[0078] The difference between Comparative Example 5 and Example 4 is that the low-carbon lithium slag composite admixture of Comparative Example 1 is used instead of the low-carbon lithium slag composite admixture of Example 1.
[0079] Comparative Example 6
[0080] The difference between Comparative Example 6 and Example 4 is that the low-carbon lithium slag composite admixture of Comparative Example 2 is used instead of the low-carbon lithium slag composite admixture of Example 1.
[0081] Comparative Example 7
[0082] The difference between Comparative Example 7 and Example 4 is that the low-carbon lithium slag composite admixture of Comparative Example 3 is used instead of the low-carbon lithium slag composite admixture of Example 1.
[0083] Comparative Example 8
[0084] The difference between Comparative Example 8 and Example 4 is that the low-carbon lithium slag composite admixture of Comparative Example 4 is used instead of the low-carbon lithium slag composite admixture of Example 1.
[0085] The lithium slag concrete of Examples 4 to 6 and Comparative Examples 4 to 8 was tested for performance indicators of working performance, mechanical properties, and crack resistance, and the sulfate ion content of the fresh concrete was determined. The sulfate ion content was determined mainly by ion chromatography. The specific testing method is as follows: the cement slurry was ultrasonically extracted with ultrapure water and centrifuged, the supernatant was purified by a solid phase extraction column, filtered through a 0.22 μm water system PES filter membrane, and the sulfate ion content in the filtrate was determined by ion chromatography, and quantified by an external standard method.
[0086] According to the provisions of GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the working performance of the fresh concrete of the embodiment and the comparative example was tested; according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete" and GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the mechanical properties and early crack resistance of the concrete were tested. The test results are shown in Table 1.
[0087] Table 1 Test results of working performance, mechanical properties and durability
[0088]
[0089] From the test results in Table 1, it can be seen that in terms of working performance, the slump of Examples 4 to 6 is ≥200mm, which has high working performance and can ensure the better construction pumpability of concrete. In terms of mechanical properties, the 28d compressive strength of Examples 4 to 6 is 52.6~54.8MPa. In contrast, the 28d compressive strength of Comparative Examples 5 and 7 is 51.5 MPa and 52.3MPa, respectively, which is smaller than that of Example 4. This shows that the calcium-type lithium slag-based synthetic zeolite framework has better stability and strength in an alkaline environment. It is widely distributed in concrete as an admixture, and can also improve the strength of concrete to a certain extent. At the same time, the lithium slag-based negative calcium mesoporous silica of the present invention has a better improvement effect on the strength of concrete. The 28d strength of Comparative Example 6 is 52.0MPa, which shows that the series of calcium-type solutions used in the preparation process of synthetic zeolite can not only improve the stability of synthetic zeolite in the alkaline environment of concrete, but also can utilize the prepared synthetic zeolite rich in calcium ions and add it to the cement base to increase the overall calcium ion concentration of concrete, accelerate the hydration reaction of concrete and improve the strength; the experimental results of Comparative Example 8 prove that the surface of negative calcium mesoporous silica is loaded with a large amount of calcium ions, which can effectively improve the alkalinity of concrete and achieve alkali excitation effect under alkaline conditions, promote lithium slag volcanic ash reaction, and improve the density of concrete.
[0090] In terms of sulfate ion content and crack resistance, the sulfate ion content and total crack area per unit area of Examples 4 to 6 were 0.25% to 0.28% and 34 to 38 mm, respectively. 2 / m 2 . The experimental results of comparative example 5 prove that the use of common commercially available synthetic zeolite and mesoporous silica to form a composite admixture with original lithium slag can only adsorb sulfate ions to a certain extent, and its overall effect on the improvement of the anti-sulfur trioxide damage effect of concrete is relatively unsatisfactory; the experimental results of comparative example 6 prove that the introduction of a large amount of calcium ions into the synthetic zeolite structure in the alkali melting stage and the hydrothermal crystallization stage can enhance the oxygen bond strength of the zeolite and reduce the relaxation effect of the bonds in the crystal framework; the experimental results of comparative example 7 prove that chlorotrihexylsilane can form Si-O-Si and Al-O-Si cross-linking bridges with Si-O bonds and Al-O bonds in the zeolite framework, enhance the stability of the zeolite framework, and improve the alkali resistance of the synthetic zeolite. Both of these can enhance the stability and strength of the synthetic zeolite framework in an alkaline environment, and enhance the adsorption and fixation ability of synthetic zeolite for sulfate ions in concrete.
[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low-carbon lithium slag composite admixture, characterized in that: The following steps are involved: S1. The lithium slag and calcium hydroxide are blended and ball-milled and then calcined and then ground to obtain a powder; S2. The powder obtained in step S1 is mixed with water, calcium aluminate and EDTA are added to adjust the molar ratio of Si / Al to obtain a mixture, and then a silane coupling agent solution is added, mixed evenly, aged and then crystallized, and a solid product and a waste liquid are obtained by filtration. The solid product is washed and dried to obtain a calcium-type lithium slag synthetic zeolite; S3. adjusting the pH value of the waste liquid of step S2 to 6-7, filtering and taking the filtrate, and adjusting the pH value of the filtrate to 3-5 to obtain a silica sol; adding the silica sol to a hexadecyltrimethylammonium bromide solution, adjusting the pH value of the mixed solution to 9-10, and then performing a polycondensation reaction, separating and washing to obtain a solid product, and then subjecting the solid product to a high temperature reaction to obtain mesoporous silica; S4. The mesoporous silica obtained in step S3 is added to a Ca(NO3)2 aqueous solution, and filtered after ultrasonic dispersion. The solid product is washed and dried to obtain lithium slag-based calcium-negative mesoporous silica; S5. The calcium-type lithium slag synthetic zeolite, lithium slag-based negative calcium mesoporous silica and original lithium slag are mixed in a mass ratio of 1:(2-6):(30-80) to obtain the composite admixture.
2. The method for preparing a low-carbon lithium slag composite admixture according to claim 1, characterized in that: In step S1, the calcination temperature is 550-600°C and the calcination time is 100-120 minutes.
3. The method for preparing a low-carbon lithium slag composite admixture according to claim 1, characterized in that: In step S2, the molar ratio of Si / Al is (2-3):1, and the mass of EDTA is 5%-10% of the mass of calcium aluminate.
4. The method for preparing a low-carbon lithium slag composite admixture according to claim 1, characterized in that: The concentration of the silane coupling agent solution is 10wt%~12wt%, and the mass ratio of the mixture to the silane coupling agent solution is (4~6):
1.
5. The method for preparing a low-carbon lithium slag composite admixture according to claim 1, characterized in that: In step S3, the temperature of the polycondensation reaction is 40-50° C., and the mixture is stirred for 10-14 hours and then allowed to stand for 10-14 hours.
6. The method for preparing a low-carbon lithium slag composite admixture according to claim 1, characterized in that: In step S3, the temperature of the high temperature reaction is 500-600° C. and the time is 5-6 hours.
7. The method for preparing a low-carbon lithium slag composite admixture according to claim 1, characterized in that: In step S4, the mass ratio of the mesoporous silica to the Ca(NO3)2 aqueous solution is 1:(2-3), and the concentration of the Ca(NO3)2 aqueous solution is 0.7-1.0 mol / L.
8. The method for preparing a low-carbon lithium slag composite admixture according to claim 1, characterized in that: The specific surface area of the original lithium slag is 400-600m 2 / kg, the specific surface area of the calcium type lithium slag synthetic zeolite is 3000-4000 m 2 / kg, the specific surface area of the lithium slag-based negative calcium mesoporous silica is 11000-13000 m 2 / kg.
9. The low-carbon lithium slag composite admixture prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The composite admixture comprises calcium-type lithium slag synthetic zeolite, lithium slag-based negative calcium mesoporous silica and original lithium slag.
10. A lithium slag concrete made from the low-carbon lithium slag composite admixture according to claim 9, characterized in that: The invention comprises the following components in parts by weight: 100-150 parts of cement, 325-440 parts of low-carbon lithium slag composite admixture, 10-15 parts of corn protein solution, 950-1100 parts of crushed stone, 700-780 parts of sand, 140-155 parts of water and 6-9 parts of water reducing agent.
Citation Information
Patent Citations
Preparation method of lithium slag concrete
CN111646773A
A kind of lithium mica slag concrete
CN115872695B
Porous self-loading zeolite material prepared from acid-process lithium slag as well as preparation method and application of porous self-loading zeolite material
CN111018422A
Modified lithium slag composite mineral admixture and preparation and application thereof
CN112079589A
Preparation method and application of mesoporous adsorbent
CN116237008A
Cited By
Comprehensive recovery method of lithium slag
CN120714773A
Multi-solid-waste modified lithium slag powder low-carbon concrete and preparation method thereof
CN122301513A